HUBUNGAN ANTARA SELF-EFFICACY DAN HARAPAN MASA DEPAN DENGAN ADAPTABILITAS KARIR PADA MAHASISWA TINGKAT AKHIR - Rizka Bella Herdiana Putri; Ridwan Budi Pramono (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the relationship between self-efficacy and future hope with career adaptability among final-year students, given the rising number of unemployed university graduates and the rapid transformation of the world of work driven by automation and digitalization. A quantitative approach with a correlational design was employed. The participants were 106 final-year students in Indonesia selected through purposive sampling. Data were collected using career adaptability, self-efficacy, and future hope scales distributed via Likert-scale questionnaires through various social media, and analyzed using multiple regression and product-moment correlation with the aid of JASP 0.96 for Windows. The findings revealed a highly significant positive relationship between self-efficacy and future hope simultaneously with career adaptability (R=0.828; p<0.01). Partially, self-efficacy was positively related to career adaptability (R=0.764; p<0.01), as was future hope (R=0.747; p<0.01), with both variables contributing 68.6% to career adaptability. This study contributes empirically by integrating self-efficacy and future hope as psychological factors shaping career adaptability, while also serving as a foundation for higher education institutions in designing career development programs oriented toward students’ psychological aspect.